Effects of Stem Mal-alignment in The Primary Stability of Total Hip Arthroplasty / Shahrul Hisyam Marwan ...[et al.] - Marwan, Shahrul Hisyam; Tardan, Giha; Zainal, Muhammad Syafiq; Abdullah, Abdul Halim (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2019)
Total hip arthroplasty is a surgical procedure to reform the hip joint by replacing the joint with femoral components. Issue of stem malalignment at varus and retroversion degree angles during the procedure had influenced the performance of the arthroplasty especially in revision surgery. Thus, the purposes of the study are to develop the finite element models of total hip arthroplasty and to investigate the effects of stem malalignment in the primary stability of the femur and hip prosthesis. Two cases of malalignment stems at varus +3 degree and varus -3 degree were reconstructed while proper aligned or straight stem was set as reference. The static analysis presenting walking and stair climbing activities is conducted using commercial computational design and analysis software. The effects of stem malalignment in the femur are discussed on the resulting stress distributions and total deformation. Higher stress magnitude was predicted in both malalignment cases as compared to the straight case. The malalignment conditions also contribute to larger displacement at the distal end of the prosthesis which can lead to implant loosening.